2020
DOI: 10.1097/sla.0000000000004125
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine for Surgical Consultations – Pandemic Response or Here to Stay?

Abstract: This study aims to determine the public's perception of telemedicine surgical consultations, during the COVID-19 pandemic and beyond. Summary Background Data: With rapid expansion and uptake of telemedicine during the pandemic, many have posited that virtual visits will endure even as in-person visits are reinstated. The public's perception of telemedicine for an initial surgical consultation has not been previously studied. Methods: A 43-question survey assessed respondents' attitudes toward telemedicine for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
78
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 18 publications
3
78
1
Order By: Relevance
“…Several studies have reported interesting perspectives of telemedicine in the surgical context, especially due to economic benefit, reduced missed work and reduced trips to hospital [ 9 11 ]. A survey on public’s perception of telemedicine showed that it was an acceptable substitute for in-person visits, especially during the pandemic [ 10 ]. It must be mentioned too that some providers worked in disciplines that were not their areas and were probably less comfortable in.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported interesting perspectives of telemedicine in the surgical context, especially due to economic benefit, reduced missed work and reduced trips to hospital [ 9 11 ]. A survey on public’s perception of telemedicine showed that it was an acceptable substitute for in-person visits, especially during the pandemic [ 10 ]. It must be mentioned too that some providers worked in disciplines that were not their areas and were probably less comfortable in.…”
Section: Discussionmentioning
confidence: 99%
“…In the surgical field, recent evidence suggests high enthusiasm for telemedicine from both patients and providers. However, concerns arise in respect to the quality of care delivered and the safety of this practice for postoperative care clinics [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous experiences with telemedicine in postoperative care have demonstrated safe and effective wound care, postoperative patient education and even ileostomy output management [ 10 , 11 ]. However, most patients and providers prefer in-person postoperative visits during normal times [ 9 ]. COVID-19 social distancing protocols have encouraged many patients to seek remote medical attention even after major surgery.…”
Section: Discussionmentioning
confidence: 99%
“…As COVID-19 emerged, both providers and patients, regardless of their prior training or comfort with telehealth, have been forced to provide or receive care remotely whenever possible. Sorensen et al 12 recently conducted a public survey to understand current perceptions on virtual care during the COVID-19 pandemic. The authors identified a high degree of public satisfaction with telehealth visits, but noted that the current elevated preference for virtual care would decrease once socialdistancing guidelines loosen.…”
Section: Introductionmentioning
confidence: 99%